Silicone/graphene oxide co-cross-linked aerogels with wide-temperature mechanical flexibility, super-hydrophobicity and flame resistance for exceptional thermal insulation and oil/water separation - Zhang, Zhao-Hui; Chen, Zuan-Yu; Tang, Yi-Hao; Li, Yu-Tong; Ma, Dequan; Zhang, Guo-Dong; Boukherroub, Rabah; Cao, Cheng-Fei; Gong, Li-Xiu; Song, Pingan; Cao, Kun; Tang, Long-Cheng (Journal of materials science & technology, 2022)
•Uniformly dispersed GO sheets in silane aqueous were obtained after APTES silane surface functionalization.•The co-cross-linked FGO/silicone interconnected network was constructed at a facile ambient-temperature drying process.•The FGO/silicone co-cross-linked aerogels showed wide-temperature mechanical flexibility, super-hydrophobicity and excellent flame retardancy.•The multifunctional aerogels are promising as exceptional thermal insulating and efficient oil/water separation materials. Development of multifunctional and high-performance silicone aerogel is highly required for various promising applications. However, unstable cross-linking structure and poor thermal stability of silicone network as well as complicated processing restrict the practical use significantly. Herein, we report a facile and versatile ambient drying strategy to fabricate lightweight, wide-temperature flexible, super-hydrophobic and flame retardant silicone composite aerogels modified with low-content functionalized graphene oxide (FGO). After optimizing silane molecules, incorporation of γ-aminopropyltriethoxysilane functionalization is found to promote the dispersion stability of GO during the hydrolysis-polymerization process and thus produce the formation of unique strip-like co-cross-linked network. Consequently, the aerogels containing ∼2.0 wt% FGO not only possess good cyclic compressive stability under strain of 70% for 100 cycles and outstanding mechanical reliability in wide temperature range (from liquid nitrogen to 350 °C), but also display excellent flame resistance and super-hydrophobicity. Further, the optimized silicone/FGO aerogels display exceptional thermal insulating performance superior to pure aerogel and hydrocarbon polymer foams, and they also show efficient oil absorption and separation capacity for various solvents and oil from water. Clearly, this work provides a new route for the rational design and development of advanced silicone composite aerogels for multifunctional applications.